2015
DOI: 10.1002/anie.201505531
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Boxes: Rationally Designed Porous Organic Cages

Abstract: The porphyrin boxes (PB-1 and PB-2), which are rationally designed porous organic cages with a large cavity using well-defined and rigid 3-connected triangular and 4-connected square shaped building units are reported. PB-1 has a cavity as large as 1.95 nm in diameter and shows high chemical stability in a broad pH range (4.8 to 13) in aqueous media. The crystalline nature as well as cavity structure of the shape-persistent organic cage crystals were intact even after complete removal of guest molecules, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 61 publications
3
134
0
5
Order By: Relevance
“…and triamines by Hong et al (for which crystal structures are available); the resultant molecules showed selectivity for small gases. 68 The range of shapes possible for the Tet 6 Tri 8 topology spans from a rhombic dodecahedron 32 through an octahedron to a cube 68 as shown in Fig. 13.…”
Section: Tetratopic + Tritopic Topology Familymentioning
confidence: 99%
“…and triamines by Hong et al (for which crystal structures are available); the resultant molecules showed selectivity for small gases. 68 The range of shapes possible for the Tet 6 Tri 8 topology spans from a rhombic dodecahedron 32 through an octahedron to a cube 68 as shown in Fig. 13.…”
Section: Tetratopic + Tritopic Topology Familymentioning
confidence: 99%
“…An established pathway to spherical structures involves the careful design and synthesis (often multi-stage) of an organic ligand with precisely spaced functional groups. Nanocapsules can be produced via reversible covalent bonds such as disulfide1314, boronic esters1516 and imines171819202122 or supramolecular interactions such as coordinative bonds23242526 and hydrogen bonding2728293031, the last being exemplified in the present work.…”
mentioning
confidence: 97%
“…Isostrukturelle Reihen von Käfigen liefern tiefere Einblicke in Struktur-Porositäts-Beziehungen. [108,299,300] Sowohl COFs als auch Käfige haben sich mittlerweile als permanent porçse Materialien etabliert, und auf den ersten Blick gibt es keine offensichtliche Präferenz füre ine der beiden Materialklassen. [138] In geordneten Phasen sind jedoch grçßere Unterschiede zu beobachten, die auf einen signifikanten Beitrag von extrinsischer Porositäti nfolge des unterschiedlichen Packungsverhaltens im Kristall schließen lassen.…”
Section: Porositätu Nd Gasspeicherungunclassified